2020
DOI: 10.1590/1806-908820200000022
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Operational Analysis of Mechanized Forest Implementation

Abstract: Mechanization in forestry implantation demands high energy, time, and high operational and production costs. Thus, studies related to the influence of variables on the efficiency of these activities are essential to reduce costs and optimize operations. The objective of this study was to evaluate the operational and cost performance of mechanized forest implantation operations in Eucalyptus sp. Data were collected from eucalyptus plantations located in the northern region of the state of Espírito Santo, Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although it is a notably profitable sector, forestry production at competitive levels requires considerable investments, especially in the logistical realm, which is considered the most delicate and impactful production stage, potentially representing up to 60% of the value of the wood produced and traded (Fiedler et al, 2020). Thus, a dilemma arises in the operational process of wood production, concerning the need to reduce these costs, particularly in the harvesting/extraction and transportation stages, while increasing productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is a notably profitable sector, forestry production at competitive levels requires considerable investments, especially in the logistical realm, which is considered the most delicate and impactful production stage, potentially representing up to 60% of the value of the wood produced and traded (Fiedler et al, 2020). Thus, a dilemma arises in the operational process of wood production, concerning the need to reduce these costs, particularly in the harvesting/extraction and transportation stages, while increasing productivity.…”
Section: Introductionmentioning
confidence: 99%
“…An example is provided for implementing a blockchain based forest management system (Frosini et al, 2009). Fiedler, et al (2020) analyzed the entire process cost of forest planting operations by studying variables related to agricultural planting mechanization, and found that the consumption cost of subsoil is the highest, indicating the need for rational utilization of existing forest areas, which can to some extent reduce the cost of seedling cultivation. This will directly affect the survival rate of afforestation and the newly formed forest area in forest resource management.…”
Section: Introductionmentioning
confidence: 99%